Analyzing Employee Performance at Alcoffee Co-working Space - Stella Stella; Evi Silvana Muchsinati (Universitas Internasional Batam, 2023)
Alcoffee Co-working Space opened for the first time in Batam on April 1, 2021. Alcoffee Coworking Space is a cafe engaged in the culinary coffee field located on Jalan Harbor bay, Batam. Compensation and benefit factors are still the main factors causing employee job satisfaction. However, job satisfaction is a condition that determines the company's success in achieving its goals. This compensation and benefits can be given to employees in the form of bonuses that can improve work performance; therefore, the method applied to the Alcoffee Co-working Space is to distribute questionnaires as data collection and observation methods by visiting. From these results, sound quality can be developed with innovations that will be provided and improve employee performance.